Прогнозні моделі науково-інноваційного розвитку Росії - Тоцька, Олеся Леонтіївна; Тоцкая, Олеся Леонтьевна; Totska, Olesia Leontiivna (My University, 2011)
Побудовано прогнозні моделі показників науки та інновацій у Росії. Отримано прогнози методом експоненційного згладжування Брауна на п’ять років. Для автоматизації розрахунків використано програмний пакет Statgraphics 2.1. Построено прогнозные модели показателей науки и инноваций в России. Получено прогнозы методом экспоненциального сглаживания Брауна на пять лет. Для автоматизации расчетов использовано программный пакет Statgraphics 2.1. The forecast models of the indicators of science and innovations in Russia is built. Forecasts by the Brown’s exponential smoothing method to five years is received. For automation of calculations a programmatic package Statgraphics 2.1 is used.
Прогнозные модели научно-инновационного развития России
Forecast models of the scientifically-innovation development of Russia
Keywords: прогнозування; прогнозирование; prognostication; наука; наука; science; інновації; инновации; innovations; моделі; модели; models; показники; показатели; indicators; Росія; Россия; Russia